Prone positioning in pediatric acute respiratory distress syndrome: a systematic review and meta-analysis of randomized controlled trials - Al-Sofyani, Khouloud Abdulrahman; Uddin, Mohammed Shahab; Alasnag, Manal (Frontiers in Pediatrics, 2026)
IntroductionAcute respiratory distress syndrome (ARDS) in children, characterized by acute lung inflammation and impaired gas exchange, presents unique therapeutic challenges due to developmental differences in respiratory physiology. While prone positioning is established in adult ARDS management, its efficacy in pediatric populations remains debated.MethodsWe conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) evaluating prone vs. supine ventilation in children and adolescents (0–18 years) with ARDS. Databases including PubMed, MEDLINE, Embase, CINAHL and CENTRAL were searched up to October 29, 2025. Methodological quality was assessed using the Cochrane risk-of-bias tool, and statistical synthesis was performed in R.ResultsThirteen RCTs (1,529 patients) were included. A meta-analysis of ten trials demonstrated a lower risk of death with prone compared with supine ventilation [risk ratio (RR) 0.67, 95% confidence interval (CI) 0.57–0.79; P = 0.0443]. Prone positioning also improved oxygenation, with a mean difference (MD) in PaO₂/FiO₂ ratio of 33.37 mmHg (95% CI 19.07–47.68). The duration of mechanical ventilation was slightly shorter in the prone group (MD = 0.90; 95% CI: 0.82–0.99), but the effect size was small and of uncertain clinical relevance, and there was no clear reduction in intensive care unit length of stay. Heterogeneity was moderate for mortality (I2 = 53.6%) and substantial to extreme for oxygenation outcomes (I2 > 90%). Funnel plots did not show marked asymmetry, although the limited number of trials reduces the power to exclude publication bias.ConclusionProne positioning may reduce mortality and improve oxygenation in pediatric ARDS, but does not clearly shorten mechanical ventilation duration or ICU stay. These potential benefits support considering prone positioning as an adjunctive strategy in pediatric critical care protocols, while underscoring the need for larger, high-quality RCTs to refine patient selection and optimize implementation strategies.